A Model for Cooperative Intelligent Transport Diffusion Simulation in the European Vehicle Fleet - Thibault Degrande; Frederic Vannieuwenborg; Sofie Verbrugge; Didier Colle (International Telecommunications Society (ITS), 2022)
To date, the European Commission is working hard on amending Directive 2010/40/EU, in which a new, technologyneutral framework for Cooperative Intelligent Transportation Systems (C-ITS) is proposed. C-ITS promise to reduce traffic congestion, lessen the environmental impact of transportation, and reduce the number of traffic mortalities. To realize those societal goals, adoption of C-ITS in passenger cars is essential. As passenger cars are no fast-moving consumer goods and the European fleet is subject to principles such as production cycles, traditional adoption models are not suitable to estimate expected penetration of C-ITS the fleet. Therefore, this paper provides a model to simulate penetration rates of C-ITS equipped cars in the European passenger car fleet, allowing simulation of both ITS-G5 and C-V2X technology diffusion separately. The model enables the assessment of the impact of policies such as a mandate, market decisions, and other scenarios, on the penetration of CITS in the European fleet. Insights into C-ITS penetration are valuable for a number of stakeholders, such as national and local governments, road authorities, car manufacturers and (network) technology providers, to appraise policy and business decisions. Lastly, the model can also be used to estimate penetration of other new technologies in passenger cars.
Keywords: 330; techno-economic; adoption; cooperative intelligent; transport systems